SCIENTIFIC ARTICLE ON REACTIVE POWER COMPENSATION ANALYSIS OF DC GENERATORS - Pakhratdinov , Asamatdin Djoldasbaevich; Maulenova , Zaurexan Axmet qızı; Jaksılıkova , Aziyza Konısbaevna (Educational Research in Universal Sciences, 2024)
This paper comprehensively analyzes reactive power compensation in systems incorporating DC generators. While DC generators inherently do not produce reactive power, their integration with AC systems necessitates effective reactive power management. Various compensation methods, including capacitor banks, synchronous condensers, and power electronic converters, are explored to enhance system stability and efficiency. Simulation results and practical implementations are discussed to provide insights into optimal strategies for reactive power compensation.